Decision Analysis on the Default Lawsuit Against the Tri Handayani Boutique Investment Contract, Supreme Court Decision NO. 13/PDT.G/2023/PN LGS - Zammara, Aurel Meidina; Suprobo, Farrel Rajendra; Lubis, Yasmin Arinda; Tarina, Dwi Desi Yayi (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2024)
Cases of default in an investment contract are an event that often occurs in Indonesia. Default is a condition where one party in a contract cannot fulfill some or all of the provisions stated in the contract. Default events require a more in-depth explanation so that we can easily understand all aspects of a default event. In Decision No. 13/Pdt. G/2023/PN Lgs, it is clear that incidents of default still occur frequently in Indonesia. Default can cause losses in both material and immaterial forms to the victim. Therefore, the author's aim in conducting this analysis is to provide an in-depth understanding of default in Indonesia.